The Effectiveness of Simple Present Tense Cubes in Improving Elementary School English Learning Outcomes: Efektivitas Kubus Simple Present Tense dalam Meningkatkan Hasil Belajar Bahasa Inggris Sekolah Dasar - Mujibburohim, Muhammad; Rochmah, Eliya (UIN Raden Mas Said Surakarta, 2025)
English learning outcomes in elementary school tend to be low because this subject has just been reintroduced into the Merdeka Curriculum. This study aims to examine the effectiveness of using Simple Present Tense Cubes in improving English learning outcomes in elementary school. This Classroom Action Research was conducted in Grade III at Pamitran Public Elementary School, Cirebon City, with 26 students. The data analysis was conducted using quantitative descriptive analysis based on the N-Gain test, normality test, and paired sample t-test results from the pretest and posttest in Cycle I and Cycle II. Each Cycle represents a separate iteration of the instructional intervention. The results indicate that the N-Gain test scores for Cycle I and II were 0.5538 and 0.6201, respectively, placing the learning improvement in the medium category. The paired sample t-test results for both cycles were < 0.001, less than 0.05, confirming a significant difference. These findings demonstrate that the use of Simple Present Tense Cubes is effective in improving English learning outcomes. The results of this study are anticipated to provide a reference for teachers in choosing effective learning media for English lesson.